2013
DOI: 10.1002/bmc.2985
|View full text |Cite
|
Sign up to set email alerts
|

A validated HPLC‐PDA method for identification and quantification of two bioactive alkaloids, ephedrine and cryptolepine, in different Sida species

Abstract: A simple, rapid, accurate and reproducible reverse-phase HPLC method has been developed for the identification and quantification of two alkaloids ephedrine and cryptolepine in different extracts of Sida species using photodiode array detection. Baseline separation of the two alkaloids was achieved on a Waters RP-18 X-terra column (250 × 4.6 mm, 5 µm) using a solvent system consisting of a mixture of water containing 0.1% Trifluoroacetic acid (TFA) and acetonitrile in a gradient elution mode with detection at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…[62] Khatoon et al also reported finding ephedrine in S. acuta, S. cordata, S. cordifolia and S. rhombifolia. [64] In this publication, contrary to the report of Khatoon et al, Chatterjee et al reported the presence of only trace amounts of ephedrine and stated that the content of ephedrine is dependent on the habitat and the origin of the plant. [64] In this publication, contrary to the report of Khatoon et al, Chatterjee et al reported the presence of only trace amounts of ephedrine and stated that the content of ephedrine is dependent on the habitat and the origin of the plant.…”
Section: Ephedra and Ephedrinementioning
confidence: 66%
“…[62] Khatoon et al also reported finding ephedrine in S. acuta, S. cordata, S. cordifolia and S. rhombifolia. [64] In this publication, contrary to the report of Khatoon et al, Chatterjee et al reported the presence of only trace amounts of ephedrine and stated that the content of ephedrine is dependent on the habitat and the origin of the plant. [64] In this publication, contrary to the report of Khatoon et al, Chatterjee et al reported the presence of only trace amounts of ephedrine and stated that the content of ephedrine is dependent on the habitat and the origin of the plant.…”
Section: Ephedra and Ephedrinementioning
confidence: 66%
“…In addition, TFA can also be considered as an effective ion‐pairing reagent [44]. A rapid quantitative method for ephedrine and cryptolepine from herbs of different Sida species was proposed with TFA as mobile phase additive [45].…”
Section: Chromatographic Separation Methodsmentioning
confidence: 99%
“…was successfully analyzed on BEH Shield RP18 column with eluent containing a low concentration of ammonium acetate [23]. XTerra RP‐18 column, another stationary phase containing EPGs, was chosen to analyze ephedrine and cryptolepine from herbs of Sida species [45]. As for polar‐endcapped stationary phase, Synergi Polar RP column was utilized for quantification of isoquinoline alkaloids from herbs or roots of Chelidonium majus L. and Thalictrum foetidum L. along with cortex of Berberis species [50].…”
Section: Chromatographic Separation Methodsmentioning
confidence: 99%
“…Plant morphology and chemical analysis methods have long been used to identify plant materials containing ephedrine alkaloids (Sun et al 2004;Kim et al 2005;Li et al 2008;Chatterjee et al 2013). Nevertheless, if the diagnostic morphological features are not visible or overlooked, it is difficult to identify.…”
Section: Introductionmentioning
confidence: 99%